The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3329/seajph.v5i2.28311
|View full text |Cite
|
Sign up to set email alerts
|

A study on health-related quality of life and comorbidity among elderly population in rural Sabah, Malaysia

Abstract: Ageing is a global phenomenon. In Malaysia, a projected model estimated that the number of elderly would be 3.4 million in 2020 which is more than 10% of the population. A cross-sectional study targeted the elderly population of three villages in rural Sabah, Malaysia aimed to investigate the health-related quality of life, comorbidity, and the socio-demographic profile amongst the elderly in the community. Participants (60 years and above) were selected for face-to-face interviews using health-related quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The observed variations in HRQOL level between countries or groups may be attributed to differences in their income or educational level, health care or social support systems, or cultural differences in the conceptualization of some of the SF-36 subscale. [89151617]…”
Section: Discussionmentioning
confidence: 99%
“…The observed variations in HRQOL level between countries or groups may be attributed to differences in their income or educational level, health care or social support systems, or cultural differences in the conceptualization of some of the SF-36 subscale. [89151617]…”
Section: Discussionmentioning
confidence: 99%
“…Conjointly, securing the well-being of physical, psychological, and social health of employees assists in stabilising an organisation. However, the majority of the published studies in Malaysia have considered only factors associated with HRQOL among the population with clinical presentation and the elderly; there is still a lack of data available concentrating on the HRQOL of the working population [ 18 , 19 , 20 , 21 , 22 , 23 ]. Therefore, the present study aimed to determine HRQOL and its associated factors—namely, sociodemographic factors, lifestyle factors, and medical history—among government employees in Putrajaya, Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is influenced by socioeconomic factors and education [20]. Study has shown positive association of demographic variables like smoking status, gender, education with diseases including hearing impairment [21]. The present study was undertaken to find association between smoking and hearing loss.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 88%